Gestational Hypoxia and Blood-Brain Barrier Permeability: Early Origins of Cerebrovascular Dysfunction Induced by Epigenetic Mechanisms - Herrera, Emilio A.; González-Candia, Alejandro (Frontiers in Physiology, 2021)
Fetal chronic hypoxia leads to intrauterine growth restriction (IUGR), which is likely to reduce oxygen delivery to the brain and induce long-term neurological impairments. These indicate a modulatory role for oxygen in cerebrovascular development. During intrauterine hypoxia, the fetal circulation suffers marked adaptations in the fetal cardiac output to maintain oxygen and nutrient delivery to vital organs, known as the “brain-sparing phenotype.” This is a well-characterized response; however, little is known about the postnatal course and outcomes of this fetal cerebrovascular adaptation. In addition, several neurodevelopmental disorders have their origins during gestation. Still, few studies have focused on how intrauterine fetal hypoxia modulates the normal brain development of the blood-brain barrier (BBB) in the IUGR neonate. The BBB is a cellular structure formed by the neurovascular unit (NVU) and is organized by a monolayer of endothelial and mural cells. The BBB regulates the entry of plasma cells and molecules from the systemic circulation to the brain. A highly selective permeability system achieves this through integral membrane proteins in brain endothelial cells. BBB breakdown and dysfunction in cerebrovascular diseases lead to leakage of blood components into the brain parenchyma, contributing to neurological deficits. The fetal brain circulation is particularly susceptible in IUGR and is proposed to be one of the main pathological processes deriving BBB disruption. In the last decade, several epigenetic mechanisms activated by IU hypoxia have been proposed to regulate the postnatal BBB permeability. However, few mechanistic studies about this topic are available, and little evidence shows controversy. Therefore, in this mini-review, we analyze the BBB permeability-associated epigenetic mechanisms in the brain exposed to chronic intrauterine hypoxia.